Características clínicas y epidemiológicas de toxoplasmosis cerebral en pacientes VIH en un hospital de nivel III – Iquitos - Pinchi Tuanama, Lynn Emily (2023)
Cerebral toxoplasmosis is a prevalent infection in HIV patients, therefore this study aimed to determine the clinical and epidemiological characteristics of cerebral toxoplasmosis in HIV patients in a level III Hospital - Iquitos. This was a descriptive, non-experimental study, retrospective and cross-sectorial scope in 46 HIV patients with confirmed cerebral toxoplasmosis. Concluding that the average age was 37 years, the majority corresponds to the male sex (76.1%), with a secondary education level (63%) and come from an urban área (82.6%). Their family members were an average of 5 people per house and had 2 to 3 rooms, with a tendency to have pets (69.5%). Regarding the clinical characteristics, 86.9% had fever, 76% headache, 26% fainting, 23.9% epileptic crisis, 47.8% focal déficit and 41.3% alteration of consciousness; with an average on the Glasgow scale of 12.2. Regarding coinfections, the majority were chronic diarrea and pulmonary tuberculosis. It was found that the CD4 count is associated with headache (p=0.0462, fever (p=0.00015) and the increase in viral load (p=0.00016) was associated with fainting (p=0.00015) and altered consciousness (p=0.0262), with a significance leve lof 95% (p=0.05).